2019
DOI: 10.1038/s41561-019-0458-8
|View full text |Cite
|
Sign up to set email alerts
|

An interval of high salinity in ancient Gale crater lake on Mars

Abstract: Precipitated minerals, including salts, are primary tracers of atmospheric conditions and water chemistry in lake basins. Ongoing in situ exploration by the Curiosity rover of a thick section of Hesperian (~3.3-3.7 Ga) sedimentary rocks within Gale crater has revealed clay-bearing fluvio-lacustrine deposits with sporadic sulfate occurrences primarily as late-stage diagenetic veins and concretions. Here, we report the discovery of bulk enrichments, disseminated in the bedrock, of Ca-sulfate (30-50 wt%) that occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
189
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 129 publications
(203 citation statements)
references
References 51 publications
11
189
3
Order By: Relevance
“…The Sutton Island member of the Murray formation, where many potential chloride observations occur, is a package of heterolithic mudstones and sandstones likely deposited in lake and lake‐margin environments dominated by suspension fallout with less common traction deposits (Fedo et al, ). Bedrock enrichments of >30 wt.% Ca and Mg sulfates in Sutton Island and Blunts Point signal some of the beds may have formed in salty waters concentrated by evaporation (Rapin et al, ; submitted). Concretions and vertical and cross‐cutting Ca‐sulfate veins are common in the Sutton Island member and signify late diagenesis (Fedo et al, ; Rapin et al, ; submitted).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Sutton Island member of the Murray formation, where many potential chloride observations occur, is a package of heterolithic mudstones and sandstones likely deposited in lake and lake‐margin environments dominated by suspension fallout with less common traction deposits (Fedo et al, ). Bedrock enrichments of >30 wt.% Ca and Mg sulfates in Sutton Island and Blunts Point signal some of the beds may have formed in salty waters concentrated by evaporation (Rapin et al, ; submitted). Concretions and vertical and cross‐cutting Ca‐sulfate veins are common in the Sutton Island member and signify late diagenesis (Fedo et al, ; Rapin et al, ; submitted).…”
Section: Discussionmentioning
confidence: 99%
“…Most of Gale's sedimentary rocks examined so far formed in a fluvio‐lacustrine environment, including both fluvial/alluvial deposits and laminated mudstones from subaqueous deposition (Grotzinger et al, ; Hurowitz et al, ; Rivera‐Hernández et al, ). Ca‐sulfates containing boron (Gasda et al, ), Mg‐sulfates (Rapin et al, ; submitted), desiccation features (Stein et al, ), and clay chemistries (Bristow et al, ) reported in Gale indicate past episodes of lake drying or lake level drop. Orbital surveys have not detected chlorides within Gale, but they are found in the nearby watershed of Sharp crater (Ehlmann & Buz, ).…”
Section: Introductionmentioning
confidence: 99%
“…Here, bulk refers to observation points that are representative of the local bedrock geochemistry without later‐stage localized diagenetic features. The point classification is primarily based on careful examination of associated context images, which enables identification of Ca‐sulfate veins (Nachon et al, 2014, 2017) as well as concretions and/or layers that differ from the surrounding bedrock (Meslin et al, 2018; Rapin et al, 2019; Sun et al, 2018). In addition to visual inspection, the recorded geochemistry of each point is also used to support the point classification.…”
Section: Methods and Observation Point Classificationmentioning
confidence: 99%
“…Sulfurous and saline waters are proposed to have existed on the surface of Mars during the Noachian-Hesperian transition (4.1-3.0 Gya) [1][2][3][4][5][6] , whereby in the Noachian period, liquid water formed widespread surface features, such as stream beds and sedimentary deposits, and led to the depositions of clay minerals 4 . Many locations on Mars feature rock formations rich in sulfur species, with sulfate and sulfide minerals detected by lander missions [7][8][9][10][11] and within martian meteorites [12][13][14][15][16] .…”
mentioning
confidence: 99%